(untitled) (مجلة إحالات, 2025)
ملخص البحث: سنحاول في هذه الورقة البحثية أن نلامس النسق الحجاجي من خلال مرثية أبي البقاء الرندي الأندلسي، هادفين استقصاء ما أمكن من الصور البلاغية التي لها الأثر الفاعل في تعزيز الحجاج وما تحدثه هذه الأخيرة من تأثيرات في المتلقي، فإذا أراد المرسل أن يرصد حركية الحجاج من ناحيته البلاغية، عليه أن يترصده ضمن ثالوث علوم البلاغة (البيان والبديع والمعاني)، وعلى وفق ما تراه البلاغة الجديدة من أنّ هذه الأنواع الثلاثة ترتبط بقضية يحاول الباث التأثير في المستقبل واستمالته، بحيث تجعله يغير موقفه، أو يذعن لموقف المرسل، فالغاية من هذه العلوم وسيلة وهدف. إنّ الفنون البلاغية – وهي كثيرة جدّا – مثل: (التقابل، الالتفات، الاستعارة، التمثيل، التفريع...) تعتبر آليات بلاغية؛ حاملة للحجاج، وفي الوقت ذاته تساهم في الإمتاع، لأنّ هدفها الأسمى هو التركيز على الفكرة ثم مراعاة الحيثيات التداولية المحيطة بها، وانطلاقا من هذا فإنّ البلاغة عموما مسلك رئيس من مسالك الحجاج والاستدلال، وأنواعها تكتسب قوتها التأثيرية الحجاجية لأنها تخاطب العقل والإحساس على حدّ سواء. الكلمات المفتاحية: البلاغة – الحجاج –الخطاب – علوم البلاغة – مرثية أبي البقاء الرندي. Research Summary: In this paper, we will attempt to touch the dialectic pattern through the tradition of the father of the Rundi Andalusian survival, aiming to investigate as much as possible the rhetorical images that have an effective effect in the promotion of the pilgrims and the effects of the latter on the recipient. If the sender wants to monitor the movement of the pilgrims, , It should lurk within the trinity of the sciences of rhetoric (statement, and knowledge and meanings), and according to the new rhetoric that these three types are linked to the issue of trying to influence the future and to compromise, so as to make him change his position or to comply with the position of the sender, the purpose of these sciences means and purpose . The rhetorical arts - which are too many - such as: (met, attention, metaphor, representation, dissociation ...) are rhetorical mechanisms, carrying pilgrims and at the same time contributing to obedience because their ultimate goal is to focus on the idea and then consider the surrounding deliberative reasoning Based on this, the rhetoric is generally the main course of the paths of pilgrims and reasoning, and their types acquire their power of the influence of pilgrims because they address both the mind and the sense. key words: Rhetoric - Pilgrims - Speech - Sciences of rhetoric - Mertia Abi stay Rundi